THE INTERACTION OF DISASTER, THE AGRICULTURAL SECTOR AND FOOD SECURITY - Soufyan, Dara Angreka; Sari Maulida Vonna; Lilis Marlina (CV. RADJA PUBLIKA, 2024)
This research explores the Interaction of Disasters and the Agricultural Sector on Food Security utilizing the Structural Equation Modeling (SEM-PLS) approach. Food security is crucial for human survival and well-being, making it a priority in any country. Indonesia has been one of the countries prone to disasters over the past decade, impacting the prevalence of food insecurity. The aim of this study is to investigate the effects of disasters on food security mediated by the agricultural sector. Sample selection involved a saturated sampling technique comprising 23 regencies/cities in the Province of Aceh. Data analysis in this research utilized SEM-PLS. The findings indicate that disasters do not influence food security, but they do affect the agricultural sector. Conversely, the research results demonstrate that the agricultural sector does not influence food security. Another significant finding in this study is that the agricultural sector does not significantly mediate the impact of disasters on food security.